Suppression of bulk conductivity and large phase relaxation length in topological insulator Bi2-delta Sn delta Te3 epitaxial thin films grown by Metal-Organic Chemical Vapor Deposition (MOCVD) - Cho, Seong Won; Kim, Kwang-Chon; Kim, Seong Keun; Cheong, Byung-Ki; Kim, Jin-Sang; Lee, Suyoun (ELSEVIER SCIENCE SA, 2017)
A topological insulator (TI), a new quantum state featured with the topologically-protected surface state (TSS) originating from its unique topology in band structure, has attracted much interest due to academic and practical importance. Nonetheless, a large contribution of the bulk conduction, induced by unintended doping by defects, has hindered the characterization of the surface state and the application of it into a device. To resolve this problem, we have investigated the transport properties of epitaxial Bi2-delta Sn delta Te3 thin films with varying delta. With the bulk conduction being strongly suppressed, the TSS is separately characterized, resulting in a large phase relaxation length of similar to 250 nm at 1.8 K. In addition, the magnetoresistance ratio (MR) has shown a non-monotonic temperature dependence with a maximum value at an elevated temperature depending on delta. These results are associated with the compensation of carriers and, we believe, provide an important step for the application of topological insulators for developing novel functional devices based on the topological surface states. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: QUANTUM OSCILLATIONS; SURFACE-STATES; BI2TE3 FILMS; MAGNETORESISTANCE